Peranan Media Sosial Sebagai Agen Sosialisasi Halal dalam Membangun Kesadaran Halal: Studi Netnografi - Miftakhul Khasanah (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2020)
This study aims to determine public behavior related to the use of social media as a source of information and knowledge about halal and the role of social media and its function as an agent of socialization to transfer knowledge and information about halal and build halal awareness in the community. This research was conducted with a Netnographic study. Netnography is an interpretive approach to study consumer behavior from various cultures and communities in cyberspace or the Internet. This approach is also referred to as